2013
DOI: 10.1128/aem.01479-13
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysin, a Novel Highly Thermostable and Cosolvent-Compatible Protease from the Thermophilic Bacterium Coprothermobacter proteolyticus

Abstract: c Through genome mining, we identified a gene encoding a putative serine protease of the thermitase subgroup of subtilases (EC 3.4.21.66) in the thermophilic bacterium Coprothermobacter proteolyticus. The gene was functionally expressed in Escherichia coli, and the enzyme, which we called proteolysin, was purified to near homogeneity from crude cell lysate by a single heat treatment step. Proteolysin has a broad pH tolerance and is active at temperatures of up to 80°C. In addition, the enzyme shows good activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 58 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, under these thermal conditions, the risk to microbial contamination is reduced [91]. Studies to characterize enzyme stability at different temperature and time incubation have revealed that thermophilic bacteria comprise some species with higher thermoactivity and stability than fungal species [91][92][93][94]. Fig.…”
Section: Thermophilic Proteolytic Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, under these thermal conditions, the risk to microbial contamination is reduced [91]. Studies to characterize enzyme stability at different temperature and time incubation have revealed that thermophilic bacteria comprise some species with higher thermoactivity and stability than fungal species [91][92][93][94]. Fig.…”
Section: Thermophilic Proteolytic Enzymesmentioning
confidence: 99%
“…With thermophilic species more tolerant at high temperature, some bacteria have produced proteolytic enzymes with recognized thermal stability, for example, Bacillus sp., which was found to sustain temperatures up to 90°C. The molecular analysis of 16 rRNA gene revealed a 99% similarity with B. amyloliquefaciens [92]; Toplak et al [93] also reported a proteolytic enzyme secreted by Coprothermobacter proteolyticus having activity at temperatures of up to 80°C, and Wilson and Remigio [94] exhibited an alkaline serine peptidase produced by a thermophilic bacterium (EP1001) with maximal activity at 75°C.…”
Section: Thermophilic Proteolytic Enzymesmentioning
confidence: 99%
“…For this two‐enzyme reaction, PAM was used first for the conversion of Z‐Gly‐Tyr‐NH 2 to the corresponding methyl ester. Subsequently, two newly described thermostable proteases Dg Sbt and Taq Sbt11 were used for coupling of the obtained Z‐Gly‐Tyr‐OMe with Phe‐NH 2 as the nucleophile (Scheme ). For a one‐pot reaction, PAM was removed by centrifugation after the first reaction, and the protease Dg Sbt was added directly to the reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The 75 kDa protease exhibited optimal activity at 70 8C and pH 2.0 and showed a half-life of 50 h at 90 8C [32]. In addition, the serine protease proteolysin from the thermophilic bacterium Coprothermobacter proteolyticus is a prominent candidate for the detergent industry because of its thermostability at elevated temperatures, its optimal activity at alkaline pH and its tolerance towards highly concentrated detergents [33].…”
Section: Proteolytic Enzymesmentioning
confidence: 99%